Development of a rapid and highly efficient Agrobacterium-mediated transformation system for pigeon pea [Cajanus cajan (L.) Millsp]. Issue 2 (3rd April 2019) - Karmakar, Subhasis; Molla, Kutubuddin Ali; Gayen, Dipak; Karmakar, Aritra; Das, Kaushik; Sarkar, Sailendra Nath; Datta, Karabi; Datta, Swapan K.
ABSTRACT: An efficient genetic transformation system is a prerequisite for studying gene functions, molecular breeding program, and introducing new traits. Agrobacterium tumefaciens- mediated genetic transformation is a widely preferred and accepted method for many plants, including pigeon pea. However, the efficiency of transformation of pigeon pea using the existing protocols is low and time-consuming. In the present study, we developed a rapid and highly efficient transformation system of pigeon pea, using embryonic axis-attached cotyledons as explants. We systematically investigated the influence of varying optical densities of Agrobacterium suspension, duration of incubation, and co-cultivation on the transformation efficiency. In our system, a transformation efficiency of approximately 83% was achieved using Agrobacterium cells at an optical density (OD600 ) of 0.25, infection time of 15 min, and co-culturing with explants for 72 h in the light with 100µM acetosyringone. The entire procedure, starting from seed to establishment of transformed plants in soil, was achieved in 35–40 days. This is a rapid and highly efficient protocol for Agrobacterium -mediated transformation of pigeon pea, which could potentially be a useful reference, not only for the genetic improvement of pigeon pea but also for other recalcitrant leguminous plants.